Analysis the Effect of Web Portal on Electronic Satisfaction - Wiry Utami; Purbo Jadmiko; Elfitra Azliyanti (AMAR (Andalas Management Review), 2019)
The study aims to analyze the effect of web portal on electronic satisfaction to Bung Hatta University Student. The Method used in this study is a quantitative method, using survey. The technique of taking sample is by using convenience sampling. Data was taken as primary data by spreading questionnaire and was measured by using Likert scale method. Methode ofanalysis used descriptive analysis and data was prosessed by using SEM SmartPLS tools. In this paper used 381 student of Bung Hatta University. The result showed that the content usefulness, adequacy of information, accessibility have not positive significant on electonic satisfaction, while usefulness and interaction have positive significant on electronic satisfaction.